Efficacy of imazethapyr applied alone and mixed with pendimethalin or imazamox in cluster bean (Cyamopsis tetragonoloba) and their residual effect on mustard (Brassica juncea) in two texturally different soils - SANGWAN, MEENAKSHI; SINGH, SAMUNDER; SATYAVAN, (The Indian Journal of Agricultural Sciences, 2016)
An experiment was carried out at two locations, CCS HAU, Hisar and farmer’s field in Kheri Batter, Bhiwani to study the efficacy and phytotoxicity of different herbicides/combinations in cluster bean (Cyamopsis tetragonoloba L.) during kharif 2013 and their carryover effect on mustard [Brassica juncea (L.) Czernj. & Coss.] crop in rabi season (2013-14). PRE application of pendimethalin 1.0 kg/ha, ready mix (RM) of pendimethalin + imazethapyr (Valor) 1.0 kg/ha and tank mix (TM) at 500 g + 50 g/ha provided 93/83, 98/90 and 100/93 % control of weeds, respectively at Hisar/Kheri Battar locations up to 30 DAS, but at 60 DAS, due to the emergence of new flush of weeds, weed control was reduced to 65/45, 83/80 and 87/87% with the above treatments, respectively at both the locations. Ready/tank mix of pendimethalin + imazethapyr (1000 g and 500+50 g/ha) not only provided satisfactory weed control up to 60 DAS but also exhibited no phytotoxic effect on cluster bean. At 60 DAS, highest weed control (88 and 87%) was recorded with imazethapyr 100 g/ha fb propaquizafop 62.5 g/ha 3 fb 6 WAS, respectively at Hisar and Kheri Battar locations which was at par with pendimethalin + imazethapyr (RM and TM), imazethapyr + imazamox (Odyssey) 70 g/ha fb propaquizafop 62.5 g/ha, 75 and 50 g of imazethapyr fb propaquizafop 3 fb 6 WAS at Kheri Battar, but the efficacy of Odyssey and imazethapyr 50 and 75 g fb propaquifzafop was lower under Hisar conditions due to heavy infestation of Trianthema portulacastrum. POE herbicides, except propaquizafop and pendimethalin showed crop phytotoxicity and growth suppression soon after application at higher rates, though plants recovered after 2 weeks and no injury was observed at later stages. Minimum weed dry weight, highest yield attributes and seed yield with maximum net return and B-C ratio was obtained under POE imazethapyr 100 g/ha fb propaquizafop 62.5 g/ha, and pendimethalin 0.5 kg + imazethapyr 50 g/ha (TM), but both were statistically similar to each other and to pendimethalin + imazethapyr (RM) 1.0 kg/ha and imazethapyr + imazamox 70 g/ha fb propaquizafop 62.5 g/ha as POE at Kheri Batter location, but at Hisar location only pendimethalin + imazethapyr (RM and TM) provided maximum net return and B-C ratio. There was no carry over effect of different herbicides used in cluster bean on succeeding mustard crop, probably due to herbicide detoxification through microbial degradation mediated by high temperature and moisture and possibly by leaching of herbicides because of 594.3 and 500.5 mm of rainfall in the crop growing season at both the locations, respectively.